Development of executive function during childhood - Yusuke Moriguchi (Frontiers Research Topics, 2016)
Executive function refers to the goal-oriented regulation of one's own thoughts, actions, and emotions. Its importance is attested by its contribution to the development of other cognitive skills (e.g., theory of mind), social abilities (e.g., peer interactions), and academic achievement (e.g., mathematics), and by the consequences of deficits in executive function (which are observed in wide range of developmental disorders, such as attention-deficit hyperactivity disorder and autism). Over the last decade, there have been growing interest in the development of executive function, and an expanding body of research has shown that executive function develops rapidly during the preschool years, with adult-level performance being achieved during adolescence or later. This recent work, together with experimental research showing the effects of interventions targeting executive function, has yielded important insights into the neurocognitive processes underlying executive function. Given the complexity of the construct of executive function, however, and the multiplicity of underlying processes, there are often inconsistencies in the way that executive function is defined and studied. This inconsistency has hampered communication among researchers from various fields. This Research Topic is intended to bridge this gap and provide an opportunity for researchers from different perspectives to discuss recent advances in understanding childhood executive function. Researchers using various methods, including, behavioral experiments, neuroimaging, eye-tracking, computer simulation, observational methods, and questionnaires, are encouraged to contribute original empirical research. In addition to original empirical articles, theoretical reviews and opinions/perspective articles on promising future directions are welcome. We hope that researchers from different areas, such as developmental psychology, educational psychology, experimental psychology, neuropsychology, neuroscience, psychiatry, computational science, etc., will be represented in the Research Topic.